PEMANFAATAN METODE NAÃVE BAYES UNTUK DIAGNOSIS TINGKAT STRES PADA MAHASISWA TINGKAT AKHIR BERBASIS DOMAIN EXPERT - YOSHUA DIMAS MEGANTARA; Latipah Latipah; Achmad Zakki Falani (SPIRIT, 2023)
Stress is something that everyone experiences in general, meaning that stress itself is a change in the body's response to threats and pressure. In dealing with stress, there are two reactions experienced by person, positive reactions and negative reactions. positive reactions can be in the form of better adaptability and increased levels of alertness and can spur these individuals to become more advanced in various matters and fields, besides the positive impact on some individuals stress can cause negative reactions which can be characterized by excessive worry, fear and feeling anxious. In living life as a student who hones knowledge in lectures according to the field taken, stress can hinder the lectures that are being undertaken, stress factors that are generally experienced by students such as bad association and relationships between fellow students or lecturers, lack of trust self, lack of support from family. Based on these problems, the authors feel the need for an expert system design to detect student stress levels with the Naive Bayes Method by taking the test location at Narotama University. The design of this expert system aims to allow students to independently diagnose the level of stress experienced. from this expert system design as much as 90% of students who do the testing get solutions from expert advice as outlined in the design of this application.